Investigation of non-smoring nicotine-containing products - T. A. Don; A. G. Mirgorodskaya; M. V. Shkidyuk; O. K. Bedritskaya (Новые технологии)
Non-smoking tobacco products are considered to be an alternative to cigarette use. Non-smoking products differ in appearance, way of consumption, ingredient composition, toxicity level, manufacturing technology, physiological effect. Recently, there has been a steady increase in the consumption of both chewing tobacco and non-tobacco nicotine-containing products in Russia. A large variety of non-smoking products creates certain problems with product identification. To determine technological and consumer characteristics (humidity, fractional composition, nicotine content) of non-smoking tobacco, methods commonly used in the tobacco industry were used. The purpose of the research is to obtain experimental data for an objective assessment of toxic load and quality characteristics of non-smoking products of the studied brands. The objects of the research are samples of non-smoking products of the following trademarks: LYFT, Captain Black, Corvus, White FOX, Skruf, Odens, CUT, Ckif, ZYN, EPOK, THUNDER. The article presents the results of studies of consumer characteristics (tasting evaluation, humidity, extraction rate, fractional composition, nicotine content) of non-smoking products. As a result of the research, identification signs of non-smoking nicotine-containing products have been established and directions for further work to assess the toxicity level of a segmental product have been determined.